Study and Evaluation of the Impact of Resettlement Patterns on Social Capital Changes in Earthquake-Stricken Villages Case study: Varzaqan County Earthquake-Stricken Villages - Vakil Heydari Sarban; Ali Majnoony Toutakhane; Mahboube Neghabi (جغرافیا و توسعه, 2016)
Earthquake occurrence  in Varzaqan county in the summer of 2012 has led to destruction of many rural areas. In order to reconstruct and prevent further financial  and human losses and Casualties,  resettlement of  some of the villages in three models of displacement, integration and reconstruction of some villages in this county was taken place. The purpose of this study is surveying the impact of triple resettlement patterns of earthquake stricken villages  on the social capital of residents of rural communities. For this purpose, three fields including  social reliability, social participation and  social correlation  were selected for the study of social capital in the study area. Statistical population of this study are the Local households living in villages of the study area which the volume of the sample was  determined by Cochran formula and simple random as 400 Households. Pilot study in similar Statistical population was performed with 50 questionnaires. The reliability of various parts of the questionnaire was obtained by Cronbach alpha special formula and obtained data as  0.895 to 0.912. Data analyses of this study in both descriptive and inferential statistics have been made by using SPSS software. To compare the pattern of displacement, integration and reconstruction,  T-test of independent samples was used.The results of this test indicate that  among the resettlement patterns ,there is a Significant differences on  0.000 level regarding the  changes' rate  of social capital. In addition, the results demonstrate that the amount of social capital with average  2.87 is greater than the two others in the reconstruction pattern. Moreover, the correlation level  between the variables of  participation and social correlation, social trust and community involvement were respectively 0.795, 0.354 and 0.324 . Eventually, according to the research findings, some Practical suggestions in fields of education, Protection, Systematic management approaches and Future studies also presented